ANALYZE OF IMPLEMENTATION CHARACTER EDUCATION POLICY BASE TO SMK N 5 MALANG STUDENT’S - Rudy Setiawan; Ismi Nurul Qomariyah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2016)
The aims of this observation to decide the analysis of policy implementation of character education in SMK N 5 Malang, includes 1) understanding and describing the implementation of Character Education Policy in SMK N 5 Malang, 2) understanding the constraints of the implementation of character education in SMK N 5 Malang, 3) finding out the school’s strategies to overcome the obstacles in the implementation of education character in SMK N 5 Malang. The study was conducted over four months using a qualitative approach. Data was collected through interviews, observations, and review documents related to this research.. Techniques of data analysis by the presentation of data, data reduction and drawing conclusions. The data analysis begins by describing the findings during the study, then discussed objectively supported by theoretical studies. The conclusion of this study is the policy implementation of education character in SMK N 5 Malang run well although there are some constraints. The obstacles are including a lack of professionalism and spirit "Among" of the teachers, the negative effects of globalization to the students, and lack of role of parents and society in the policy implementation of character education. And to overcome these obstacles, do the strategies implemented by 1) increasing the professionalism and spirit betwen the teacher, 2) implementing the methods of character education with the "mengerti, merasa, melakukan”. Keywords: Character, Education, Implementation